(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
In this article, information about the Neolithic ceramics of Uzbekistan and the research of the first pottery works at the world level is intended to be covered. In this case, the fact that pottery is the primary source in the study of the material culture of Stone Age communities, the regions of the monuments where the first ceramics were found in the world, the chronology and periodization of the monuments, the making of ceramics the factors and conditions of the emergence of technology, the process of making the oldest pottery and the social importance of their use in everyday life, as well as the results of the research of Neolithic ceramics of Uzbekistan are presented.